2018
DOI: 10.1016/j.earscirev.2017.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Pliocene stratigraphic paleobiology in Tuscany and the fossil record of marine megafauna

Abstract: Tuscany has a rich Pliocene record of marine megafauna (MM), including mysticetes, odontocetes, sirenians and seals among the mammals, and six orders of sharks among the elasmobranchs. This is reviewed with respect to paleogeography and sequence-stratigraphy in six different basins. Conditions at the ancient seafloor are explored by means of sedimentary facies analysis, taphonomy and multivariate techniques applied to a large quantitative dataset of benthic molluscs. MM is rare or absent in most basins during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 163 publications
2
40
0
Order By: Relevance
“…These characteristics include: the depression of the premaxillae in front of the premaxillary sac fossae; the constriction of the medial exposure of the maxilla between the premaxillae just posterior to the anterior end of the external bony nares; the lateral expansion of the left premaxilla anterior to the left premaxillary foramen; the very small size of the external bony nares; the triangular nasals (which are even more slender and posteriorly elongated than in D. leucas). Considering the subtropical climate conditions of the Mediterranean Sea during the early Pliocene (Bianucci et al, 2009;Prista et al, 2015;Dominici et al, 2018), the finding of MSNUP I17602 supports the hypothesis of an ancestral adaptation of Monodontidae to warm climate conditions followed by a dispersion to high-latitude environments which ultimately led to the origin of the modern monodontid genera.…”
Section: Discussionmentioning
confidence: 67%
“…These characteristics include: the depression of the premaxillae in front of the premaxillary sac fossae; the constriction of the medial exposure of the maxilla between the premaxillae just posterior to the anterior end of the external bony nares; the lateral expansion of the left premaxilla anterior to the left premaxillary foramen; the very small size of the external bony nares; the triangular nasals (which are even more slender and posteriorly elongated than in D. leucas). Considering the subtropical climate conditions of the Mediterranean Sea during the early Pliocene (Bianucci et al, 2009;Prista et al, 2015;Dominici et al, 2018), the finding of MSNUP I17602 supports the hypothesis of an ancestral adaptation of Monodontidae to warm climate conditions followed by a dispersion to high-latitude environments which ultimately led to the origin of the modern monodontid genera.…”
Section: Discussionmentioning
confidence: 67%
“…The fact that this passage coincides with the onset of the evolutionary radiation of very large baleen whales and with their almost doubling in maximum size (Marx et al, 2016) -which should instead contribute a far better record -must have also triggered the radiation of bone eaters, with the counterintuitive effect of making extremely unlikely for cetacean bones to become preserved. Modern worldwide data confirm that even the largest whale skeletons are rapidly destroyed at deep-water settings (see references in Dominici et al, 2018).…”
Section: Discussionmentioning
confidence: 86%
“…In the Pliocene of Tuscany articulated specimens and rather complete skeletons are associated with offshore mudstones deposited at an estimated depth of 30-300 m, suggesting that very shallow and very deep (bathyal) depths are generally unfavourable to the preservation of bones (Dominici et al, 2018). An analogous environmental control on the degree of articulation and completeness of fossil cetacean skeletons is also observed in the Pliocene of Emilia and Piedmont, positively correlated with offshore mudstones and biocalcarenite transgressive shell-beds, whereas no skeletons are associated with shoreface sandstones, and rare occurrences in epibathyal mudstones (Freschi & Cau, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary investigations revealed that: it belonged to the family Balaenopteridae; it does not belong to any of the living taxa; based on the length of its dentary, it was estimated that the total body length of "Brunella" should have been between c. 6 and c. 7.5 m and its weight was c. 5000 kg; the age of this whale was preliminarily assessed based on foraminifers and mollusks and was constrained between 3.7 and 4.5 Ma. "Brunella" was framed in publications on the taphonomy and stratigraphic palaeobiology of baleen whales from Italy (Dominici et al, 2009;2018). Given its degree of completeness and preservation, it is expected that "Brunella" will shed further light on the evolution of balaenopterid mysticetes from the Early Pliocene of the Mediterranean basin.…”
Section: Discussionmentioning
confidence: 99%